2020
DOI: 10.1055/s-0039-3400752
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Based on Preoperative Kambin's Triangular Working Zone Measurements on 3D CT/MR Fusion Imaging to Determine Optimal Approaches to Transforaminal Endoscopic Lumbar Diskectomy

Abstract: Background Transforaminal endoscopic lumbar diskectomy (TELD) is a widely used minimally invasive surgical procedure to treat herniated disks. Postoperative dysesthesia (POD) is a significant complication that affects patient satisfaction. Several anatomical and magnetic resonance (MR) imaging studies of the intervertebral foramina showed that TELD should be avoided in patients with small Kambin's triangular working zones. Recently, some reports indicated the usefulness of three-dimensional (3D) computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We also found that, at all levels, the boundaries of the lumbar safety triangle were smaller in the coronal oblique plane than in the coronal plane, with the mean differences between the two planes being statistically significant for almost all measures. Recent studies have performed three-dimensional computed tomography ( 44 ) and MRI reconstructions in preoperative planning software ( 15 , 45 ) , suggesting the appropriate location and safe angulation for introducing the working cannulas ( 46 ) . However, those studies have not mentioned the measurements of the lumbar safety triangle at those angulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that, at all levels, the boundaries of the lumbar safety triangle were smaller in the coronal oblique plane than in the coronal plane, with the mean differences between the two planes being statistically significant for almost all measures. Recent studies have performed three-dimensional computed tomography ( 44 ) and MRI reconstructions in preoperative planning software ( 15 , 45 ) , suggesting the appropriate location and safe angulation for introducing the working cannulas ( 46 ) . However, those studies have not mentioned the measurements of the lumbar safety triangle at those angulations.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been many studies of the lumber safety triangle in cadavers, only a few have involved the use of MRI ( 12 , 13 , 14 , 15 , 16 ) . To our knowledge, there have been no studies analyzing the dimensions of the dorsal root ganglion and its relationship with the lumbar safety triangle in different planes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, researchers have begun to test the efficacy of MRI/CT fusion to extract the benefits of both technologies. 7,45,46 Using either an artificial intelligence model or manual fusion, 3D visualizations have been created by merging MRI with CT images of the lumbar vertebrae. This methodology appears to compensate for the disadvantages of each individual scan and enables analysis of the relationship between the bony components and neural tissue of Kambin's triangle in 3D.…”
Section: Ct Is the Major Modality For Measuring Kambin's Trianglementioning
confidence: 99%
“…Consequently, there has been an interest in improving and evaluating preoperative imaging techniques to improve patient outcomes. Description of the use of 3D CT/magnetic resonance fusion imaging technique to evaluate Kambin's triangle found that the use of this technique preoperatively to acquire accurate measurements can enhance patient safety and outcomes in transforaminal endoscopic lumbar discectomy [37]. A more recent study used the same method with artificial intelligence (AI) to reduce processing time and evaluation of these preoperative studies, showing the importance of incorporating AI and deep learning to plan personalized and technically precise surgeries in the future [15].…”
Section: Preoperative Evaluation Of Kambin's Trianglementioning
confidence: 99%